1992
DOI: 10.1002/hep.1840150626
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines Tumor Necrosis Factor and Interleukin–6 in Experimental Biliary Obstruction in Mice

Abstract: The putative role of the cytokines interleukin-6 and tumor necrosis factor in the pathophysiology of the complications and mortality after surgery in jaundiced patients was studied in a murine model. Cytokine serum levels were determined in mice with experimental biliary obstruction. As an indicator of the activation status of macrophages, cytokine release by mononuclear phagocytes obtained from such mice was assessed. Following surgery, interleukin-6 levels increased to 2 to 3 ng/ml after 3 to 4 hr, but decli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
88
2
7

Year Published

1993
1993
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(107 citation statements)
references
References 32 publications
10
88
2
7
Order By: Relevance
“…23 Recently, IL-6 was reported to be produced in livers of mice subjected to bdl, 24 which is in line with earlier reports of elevated plasma levels of IL-6 in mice with experimentally induced obstructive jaundice. 11,25,26 Similar to the absence of differences between IL-1R ϩ/ϩ and IL-1R Ϫ/Ϫ mice as described here, IL-6 gene-deficient mice did not demonstrate clear phenotypic differences after bdl when compared with wild-type mice. 24 Experimentally induced obstruction of the bile duct was associated with a profoundly increased susceptibility towards endotoxin, as indicated by the occurrence of mortality after administration of endotoxin in a dose that did not cause mortality, enhanced cytokine release, or more severe liver damage in sham-operated mice.…”
Section: Discussionsupporting
confidence: 80%
“…23 Recently, IL-6 was reported to be produced in livers of mice subjected to bdl, 24 which is in line with earlier reports of elevated plasma levels of IL-6 in mice with experimentally induced obstructive jaundice. 11,25,26 Similar to the absence of differences between IL-1R ϩ/ϩ and IL-1R Ϫ/Ϫ mice as described here, IL-6 gene-deficient mice did not demonstrate clear phenotypic differences after bdl when compared with wild-type mice. 24 Experimentally induced obstruction of the bile duct was associated with a profoundly increased susceptibility towards endotoxin, as indicated by the occurrence of mortality after administration of endotoxin in a dose that did not cause mortality, enhanced cytokine release, or more severe liver damage in sham-operated mice.…”
Section: Discussionsupporting
confidence: 80%
“…20,26,[34][35][36][37][38] Mortality was significantly reduced in these animal models. With respect to the preferred route of drainage, internal PBD was found to be superior to external PBD in terms of reduction in endotoxemia and mortality by some, whereas others demonstrated external drainage, although in the shortterm, to lead to a better recovery of cellular immunity than internal drainage.…”
Section: Biliary Drainagementioning
confidence: 85%
“…[17][18][19][20][21][22] Increased concentrations of TNF, mainly produced by liver Kuppfer cells, or rather, the imbalance with its soluble receptors, as antagonists and released from the cell membrane by endotoxemia, are suggested to contribute to development of complications. 18,23 After endotoxin administration to cholestatic rats, Kennedy et al demonstrated that blockade of Kuppfer cells with gadolinium chloride leads to a lower systemic TNF activity and subsequently resulted in an improved survival.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Kupffer cells release many mediators that activate stellate cells, including TNF-α, TGF-β, human growth factor, PDGF, and reactive oxygen species [60,70] . TNF-α production and NF-κB activation increase during cholestasis [71,72] . Activation of NF-κB, probably due to oxidative stress, could lead to expression of TNF-α.…”
Section: How Does Ho-1 Overexpression Increase Cholestasis-induced LImentioning
confidence: 99%